2001
DOI: 10.1101/gad.190301
|View full text |Cite
|
Sign up to set email alerts
|

In vivo chromatin remodeling by yeast ISWI homologs Isw1p and Isw2p

Abstract: Isw1p and Isw2p are budding yeast homologs of the Drosophila ISWI chromatin-remodeling ATPase. Using indirect-end-label and chromatin immunoprecipitation analysis, we show both independent and cooperative Isw1p-and Isw2p-mediated positioning of short nucleosome arrays in gene-regulatory elements at a variety of transcription units in vivo. We present evidence that both yeast ISWI complexes regulate developmental responses to starvation and that for Isw2p, recruitment by different DNA-binding proteins controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 34 publications
13
106
1
Order By: Relevance
“…Consistent with transcriptional silencing of Pol II genes at the rDNA being a result of specialized silent chromatin, data presented here and elsewhere [7] suggest that Isw1 and Isw2 alter the function of silent chromatin at the rDNA. However, in contrast to the regulation of endogenous Ty1 elements located outside of the rDNA [20], our results suggest that ISW1 and ISW2 do not act redundantly in the silencing of Pol II-transcribed genes in the rDNA.…”
Section: Isw2 Regulates Transcriptional Silencing At the Rdnacontrasting
confidence: 87%
See 1 more Smart Citation
“…Consistent with transcriptional silencing of Pol II genes at the rDNA being a result of specialized silent chromatin, data presented here and elsewhere [7] suggest that Isw1 and Isw2 alter the function of silent chromatin at the rDNA. However, in contrast to the regulation of endogenous Ty1 elements located outside of the rDNA [20], our results suggest that ISW1 and ISW2 do not act redundantly in the silencing of Pol II-transcribed genes in the rDNA.…”
Section: Isw2 Regulates Transcriptional Silencing At the Rdnacontrasting
confidence: 87%
“…In contrast to the regulation of the Ty1his3AI-236 element in the rDNA, cells lacking either ISW1 or ISW2 individually do not exhibit defects in transcription of genomic Ty1 elements [7;20]. However, previous work has shown that cells lacking both ISW1 and ISW2 have higher levels of Ty1 transcripts than wild-type or single ISW1 or ISW2 deletion mutants, a result that suggests that Isw1 and Isw2 act redundantly to repress transcription of genomic Ty1 elements [20]. Consistent with transcriptional silencing of Pol II genes at the rDNA being a result of specialized silent chromatin, data presented here and elsewhere [7] suggest that Isw1 and Isw2 alter the function of silent chromatin at the rDNA.…”
Section: Isw2 Regulates Transcriptional Silencing At the Rdnamentioning
confidence: 99%
“…Deckert and K. Struhl, in prep. ), and recruitment of the ISW2 complex by the Ume6 repressor is important for transcriptional repression of target genes (Goldmark et al 2000;Fazzio et al 2001;Kent et al 2001). However, the connection between activatorand repressor-dependent recruitment to transcriptional output is not always straightforward.…”
Section: Constitutive and Regulated Recruitment Of Rsc In Response Tomentioning
confidence: 99%
“…SWI/SNF recruitment to the histone HTA1 promoter requires both Hir1 and Hir2 corepressors, although SWI/SNF contributes positively to transcription in this situation (Dimova et al 1999). The ISW2 complex is recruited to promoters by the Ume6 repressor, and it is important for repression of target genes (Goldmark et al 2000;Fazzio et al 2001;Kent et al 2001). These models are not mutually exclusive, and, indeed, histone acetylases and deacetylases have both promoter-specific and genome-wide activities (Kuo et al 2000;Reid et al 2000;Vogelauer et al 2000).…”
mentioning
confidence: 99%
“…The Isw2-Itc1p complex was subsequently shown to be involved in the repression of other genes related to the starvation response, such as INO1 (Sugiyama & Nikawa, 2001) and PHO3 (Kent et al, 2001). The ISW2 gene encodes a yeast homologue of the Drosophila ISWI chromatin-remodelling ATPase (Tsukiyama et al, 1999;Trachtulcova et al, 2000), which is essential for development as well as for cell viability (Deuring et al, 2000).…”
Section: Introductionmentioning
confidence: 99%